Decolonising tertiary psychology education in Australia: Processes, challenges, and opportunities of curricula change - Belle Selkirk; Joanna Alexi; Chontel Gibson; Rachel Fishlock; Pat Dudgeon (The Australian Journal of Indigenous Education, 2025)
Australian psychology higher education and training has historically excluded Aboriginal and Torres Strait Islander peoples’ knowledge systems which has profoundly shaped the discipline, including its cultural responsiveness. Decolonising psychology education offers a systemic approach to improve education and practice, and, in turn, the cultural responsiveness of psychology. Decolonising psychology higher education has become a focal point to support transformational change. The present research investigated how higher education providers (HEPs) are decolonising psychology education in Australia. An Aboriginal Participatory Action Research approach was used to design, implement and evaluate the research. Eighteen representatives of psychology HEPs completed a short, open-ended survey. Findings were thematically analysed via qualitative content analysis. Results highlighted 11 interconnecting themes ranging from effective policies to adequate resourcing. The results demonstrated the need for ongoing Indigenous leadership, resourcing and systemic changes that value Indigenous ways of knowing, being and doing to support efforts in decolonising psychology education.